The Influence of Non-Performing Loans, Loan to Deposit Ratio and Interest Rates on The Proportion of Micro, Small And Medium Business Credit (MSMEs) In Indonesia - Valencia Gozali; Lindawati Lindawati; Riky Setiawan; Sehat Maruli; Juli Meliza (Yayasan Riset dan Pengembangan Intelektual, 2023)
This study aims to examine and analyze the effect of non-performing loans, loan to deposit ratio and interest rates on the proportion of micro, small and medium enterprises (MSMEs) loans in Indonesia. The research method used in this study uses a quantitative research method with a type of quantitative descriptive research that is explanatory research. The population of this study are government bank companies listed on the Indonesia Stock Exchange as many as 3 companies. In this study, Bank BTN was not included because the financial statements from Bank BTN were not completely available. The data analysis method used is multiple linear regression. The results of the f test study where the probability results are 0.009145 <0.05 indicating that simultaneously Non Performing Loans, Loan to Deposit Ratios and Interest Rates affect the Proportion of Micro, Small and Medium Enterprises Credit (Case Study at Government Banks) in Indonesia. The results of the t-test research where Non-Performing Loans, Loan to Deposit Ratio and Interest Rates have no influence on the Credit Proportion. The results of the analysis of the coefficient of determination obtained an Adjusted R2 value of 0.278650, meaning that the variations in the Non Performing Loans, Loan to Deposit Ratio and Interest Rate variables are 27.86%, while the remaining 72.14% is explained by other variables.